Das Denken des Denkens: Ein philosophischer Überblick - Soboleva, Maja (transcript, 2016)
A Renaissance of thinking – the essays in this volume analyze the recent rediscovery of thinking by philosophy. Can the investigation of the semantic field surrounding the term »thinking« actually open up a new understanding of it?